SURFACE MODIFICATION ON ZLH-DS-ISO NANOCOMPOSITE FOR CONTROLLED RELEASE AND KINETIC BEHAVIOUR OF ISOPROCARB ANION - Muda, Zuhailimuna; Hashim, Norhayati; Bakar, Norlaili Abu; Isa, Illyas Md; Mahamod, Wan Rusmawati Wan; Sharif, Sharifah Norain Mohd; Bakar, Suriani Abu; Mamat, Mazidah; Zobir, Syazwan Afif Mohd; Zainul, Rahadian (CENTRAL ASIA AND THE CAUCASUS, 2022)
A nanocomposite is a material with a nanoscopic size of 10-9m formed from a combination of two or more different materials that have the properties of blended materials. Surface modification of zinc layered hydroxide-dodecyl sulphate-isoprocarb (ZLH-DS-ISO) nanocomposite with chitosan and cellulose acetate was studied, and so is their release behaviour. A powder X-ray diffraction (PXRD) pattern for the intercalation peak showed a d-spacing value of 3.31 nm for both ZLH-DS-ISO nanocomposites coated with chitosan and cellulose acetate. The FTIR spectra of coated nanocomposites showed the existence of both chitosan and cellulose acetate. The controlled release of ISO from ZLH-DS-ISO nanocomposite coated with chitosan showed slow release compared to ZLH-DS-ISO nanocomposite coated with cellulose acetate. The kinetic behaviour of ISO from ZLH-DS-ISO nanocomposite coated with chitosan is governed by first-order for Na3PO4 solution and parabolic diffusion for both Na2SO4 and NaCl solutions. Meanwhile, the kinetic behaviour of ISO anion from ZLH- DS-ISO nanocomposite coated with cellulose acetate follows a pseudo-second-order for all Na3PO4, Na2SO4 and NaCl solutions. These polymeric coated nanocomposites, consisting of organic-inorganic nanolayers, showed enhanced release performance compared to uncoated nanocomposites. This study will be beneficial in promoting a good work environment by ensuring the safer use of insecticide by workers and users.